The Relationship between Hba1c Level and Total Cholesterol in Type 2 Diabetes Patients - Wulandari A, Made Ayu Meita (Journal La Medihealtico, 2025)
Type 2 diabetes mellitus (T2DM) is a global health challenge with cardiovascular complications as the leading cause of morbidity and mortality. Monitoring HbA1c levels and lipid profiles are crucial parameters in evaluating cardiovascular risk in T2DM patients. This cross-sectional analytical study was conducted at the Gianyar Police Clinic from January to June 2024. A total of 60 T2DM patients meeting the inclusion criteria were analyzed using Pearson correlation and multiple linear regression tests to assess the relationship between HbA1c levels and total cholesterol. A significant positive correlation was found between HbA1c levels and total cholesterol (r=0.458, p<0.001). The correlation was stronger in patients with diabetes duration >10 years (r=0.512, p<0.001). 73.3% of patients had HbA1c >7% and 56.7% experienced total cholesterol abnormalities. Statin use showed a weaker correlation (r=0.378) compared to non-users (r=0.526). The majority of patients were in the 50-65 years age group (56.7%), with 63.3% having hypertension and 40% experiencing obesity as comorbidities. There is a significant relationship between HbA1c levels and total cholesterol in T2DM patients, with the strength of the relationship influenced by diabetes duration, statin use, and comorbidities. These findings emphasize the importance of simultaneous monitoring of both parameters in T2DM management, considering local socio-cultural factors.